Deteksi Molekuler Bakteri Patogen pada Makanan Fermentasi Tempe Dage berdasarkan marka gen 16S rRNA - Eshananda, Yuriza; Fikriyya, Nabela; Fadlilah, Synta Haqqul (Agropross : National Conference Proceedings of Agriculture, 2023)
Tempe Dage is fermented food product originating from Banyumas Regency, Central Java. The appearance of Dage tempeh is slightly different from tempeh in general with lots of black spots on its surface. Even though it is often consumed by the people of Banyumas, there is no information regarding the presence of pathogenic bacteria in Dage tempeh which have the potential to harm human health. Therefore, this study aims to detect the diversity of pathogenic bacteria in the Tempe Dage microbiome using the Next Generation Sequencing (NGS) approach. The research steps were from bacterial culture with Reasoner’s 2A (R2A) medium, genomic DNA extraction, Ilumina platform-based sequencing based on the Variable region of the 16S rRNA gene, and bioinformatics analysis. The results of bioinformatics analysis on the EZBioCloud webserver (https://www.ezbiocloud.net/contents/16smtp) showed that the Dage tempe samples contained several pathogenic bacteria which were detected, such as Escherichia coli, Enterococcus faecalis, Staphylococcus aureus, Vibrio metschnikovii and Salmonella bongori. These results provide novel information regarding the presence of pathogenic bacteria in traditional Dage food which can be further analyzed using a conventional culture approach.